1998
DOI: 10.3759/tropics.7.223
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Tropical Rainforests Based on Potential Natural Vegetation Species for Degraded Areas in Sarawak, Malaysia.

Abstract: ABSTRACT. A rehabilitation study of tropical rainforesls in Sarawak was conducted in lwo phases, namely a phytosociological study and stand-establishment sludies, the phases run conseculively. Two vegelation communities were recognized: a Cyrtostachys lakka -Whiteodmdron moultinnun community and a Hopea kerangasutsis -Allantospennwn borneense cornmunity. All the species for the planting trial were collected from the Hopea kerangasensis -Allantospermum bomeense community, which has been recognized as the PNV at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…One technique has been carried out in Bintulu, Sarawak using mixed dense planting method for rehabilitating degraded shifting cultivation area (Miyawaki, 2010). The indigenous tree species recommended were Shoreaovata, S. macrophylla, S. mecistopteryx, Dryobalanops aromatica, Parashorea parvifolia, Hopea beccariana, Durio carinatus and Eusideroxylon zwagery (Alias et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One technique has been carried out in Bintulu, Sarawak using mixed dense planting method for rehabilitating degraded shifting cultivation area (Miyawaki, 2010). The indigenous tree species recommended were Shoreaovata, S. macrophylla, S. mecistopteryx, Dryobalanops aromatica, Parashorea parvifolia, Hopea beccariana, Durio carinatus and Eusideroxylon zwagery (Alias et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, frequent heavy rainfall might have caused a severe erosion of the surface soil and therefore subsurface soils became a current surface layer. Alias et al (1998) stated that the soil of the study site belongs to Bekenu and Nyalau Series. According to Soil Survey Staff (1999) Bekenu Series are fine loamy red yellow podzolic group with hue color of 10YR within 50 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Several rehabilitation efforts using different technique have been carried out in Malaysia with varying degrees of success. One technique that has been successful in the warm temperate zone is dense planting (Miyawaki, 1993 (Alias et al, 1998). The soil morphological, mineralogical and sesquioxides of the rehabilitated forest are yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Hattori et al [43] in Niah Forest Reserve reported that S. macrophylla seedlings had a relatively lower growth rate for height (0.105 cm cm −1 year −1 ) and diameter (0.124 mm mm −1 year −1 ) than that of Dryobalanops beccarii (0.316 cm cm −1 year −1 and 0.328 mm mm −1 year −1 , respectively), S. parvifolia (0.328 cm cm −1 year −1 and 0.308 mm mm −1 year −1 ), and other Shorea species. In open areas of Borneo, the tree height growth of planted dipterocarp species such as S. macrophylla (461 cm after 72 months) [53], S. ovata (450 cm after 60 months) [54], and 11 other dipterocarp species (320 to 580 cm after 60 months) [55] was also reported.…”
Section: Effects Of Seedling Age On Growth After Outplantingmentioning
confidence: 99%